A mitigação dos riscos orçamentários associados à sustentabilidade econômica dos programas estratégicos do Exército Brasileiro. - Pimentel, Luiz Paulo Gomes (2022)
Government strategic planning and budget planning are two pieces of information that outline the guidelines according to which the Brazilian State will make efforts, including financial efforts, to achieve social welfare and satisfy the demands of society. Within the scope of the Ministry of Defense and the Armed Forces, the implementation of strategic National Defense programs guided the strategic and budgetary planning of the Brazilian Army. The main risks identified for achieving the objectives of the Army's strategic programs are of a budgetary nature, characterizing a risk to the economic sustainability of these programs. That being said, it is important to clarify which would be the most adequate mitigating measures for budgetary risks of the Brazilian Army's strategic programs, so that these programs achieve their physical and financial targets and economic sustainability in the long term. Therefore, the general objective of this dissertation study is to analyze the budget risks of the Brazilian Army's strategic programs, and to propose actions to address these risks by identifying the variables of studies related to budget risk management in the strategic planning of public agencies, followed by a survey of the risks identified by the managers of strategic programs, and assessment of these budget risks regarding their impact on the strategic objectives and the economic sustainability of the Brazilian Army's Strategic Programs. A dissertative study was conducted, of a deductive nature and qualitative approach, to conduct a descriptive research, with data collection from bibliographic sources, from Brazilian Federal Government databases, and from administration agents who participated in the budget execution of resources destined to the Army's Strategic Programs. The Delphi method was applied to a set of ten internal governmental auditors who are specialists in risk management and who performed audits on the Army's Strategic Programs. Twenty risks of a budgetary nature were identified and evaluated, and preventive and contingency actions were proposed for the occurrence of such risks, and the link between budgetary risks and the economic objectives and sustainability of Strategic Programs was confirmed. The main results found were the validation of some of the risk treatments cited by the researched literature for Strategic Programs, and the proposal of mitigation actions for these risks by the experts participating in the Delphi method, which constitutes a strong improvement of the preventive and contingency measures for the Army's Strategic Programs' budget risks, and that can certainly be replicated to other Armed Forces' Strategic Programs. The main conclusions were that the improvement of the budget, financial and asset execution of Strategic Programs can be used for any and all public contracting processes, that the alignment between strategic and budget planning are determinant for the achievement of an organization's objectives and goals, and that the management of budget risks contributes positively to the economic sustainability of programs and projects.